Comparative analysis of LVAD patients in regard of ischaemic or idiopathic cardiomyopathy: A propensity-score analysis of EUROMACS data. Issue 3 (March 2022) - Merkle-Storms, Julia; Djordjevic, Ilija; Sabashnikov, Anton; Eghbalzadeh, Kaveh; Gkouziouta, Aggeliki; Fiane, Arnt; Stockman, Bernard; Montalto, Andrea; Bernhardt, Alexander; Meyns, Bart; Netuka, Ivan; De By, Theo; et al.
Background: Despite recent advances in management of patients with advanced heart failure, mortality remains high. Aim of this study was to compare impact of different aetiology of ischaemic and idiopathic cardiomyopathy on early outcomes and long-term survival of patients after left ventricular assist device implantation. Methods: European Registry for Patients with Mechanical Circulatory Support (EUROMACS) gathers clinical data and follow-up parameters of LVAD recipients. Patients enrolled in the EUROMACS registry with primary diagnosis of either ischaemic ( n  = 1190) or idiopathic ( n  = 812) cardiomyopathy were included. Primary Endpoints were early mortality as well as long-term survival. Secondary endpoint were major postoperative adverse events, such as need for rethoracotomy. Additionally, a propensity-score matching analysis was performed for patients with ischaemic ( n  = 509) and idiopathic ( n  = 509) cardiomyopathy. Results: In terms of basic demographics and baseline parameters the two groups significantly differed as expected before propensity-score matching due to different aetiology of cardiomyopathy. Seven-day (52 (4.4%) versus 18 (2.2%); p  = 0.009), 30-day (153 (12.9%) versus 73 (9.0%); p  = 0.008) and in-hospital mortality (253 (19.7%) versus 123 (15.1%); p  = 0.009) were significantly lower in the idiopathic cardiomyopathy group compared to the ischaemic cardiomyopathy group, whereas after propensity-score matching 30-day ( p  = 0.169) was comparable and in-hospital mortality ( p  = 0.051) was almost significant. Kaplan-Meier survival analysis revealed no significant difference in regard of long-term survival after propensity-score matching (Breslow-test p  = 0.161 and LogRank-test p  = 0.113). Conclusion: Though patients with ischaemic and idiopathic cardiomyopathy suffer from different cardiomyopathy aetiologies, 30-day-mortality and long-term survival of both groups were similar leading to the conclusion that covariates predominately influence mortality and survival of ischaemic and idiopathic cardiomyopathies.